STRATEGI KOMUNIKASI PEMASARAN MELALUI MEDIA DARING TERHADAP KEPUTUSAN PEMBELIAN - Diana Fitriani (STIE 'INDONESIA' Pontianak, 2021)
Research on the analysis of marketing strategies through online media in Pontianak through Facebook and Instagram. Quantitative related is used for the path analysis method and the application of SPSS V. 23.0 as a calculation tool. Respond 100 with a non-probability sampling technique that is unintentional. Communication strategies in research are lead to awareness, knowledge, passions, inclinations, beliefs and purchases. Based on this strategy, a positive and significant value is obtained in the decision making process. Marketing communication strategies through online media towards consumer purchasing decisions on culinary products marketed through Instagram and Facebook. The results of the study with a significance of 0,000 obtained a beta coefficient of 0.483. The significance of tcount <0.05 indicates that Ho was not accepted and thus received Ha. Explanation of the results of calculations in research gives a meaningful and positive marketing communication strategy to the product purchase decision variable through online media. It can be concluded that the strategies proposed have proven to be effective in winning diverse consumer dynamics